STRATEGI BIMBINGAN ISLAM DALAM MEMBERIKAN LAYANAN KELUARGA BAGI MASYARAKAT DI KECAMATAN SOMBA OPU KABUPATEN GOWA - Sitti Trinurmi (Jurusan Bimbingan dan Penyuluhan Islam, 2022)
The journal that was created aims to describe how the form of Islamic guidance for the sakinah family is. The main problem contained in this research is how the Islamic Guidance Method in forming the Sakinah Family in Somba Opu District, Gowa Regency, with the sub-problem used by the researcher, namely How is the form of the implementation of Islamic Guidance for pre- and post-wedding couples in understanding the rights and obligations in marriage in Somba Opu District, Gowa Regency? What are the supporting factors and inhibiting factors in implementing Islamic Guidance for couples who want to get married (Pre-marriage) and Post-marriage (after marriage) in Somba Opu District, Gowa Regency. This study uses descriptive qualitative research located at KUA (Religious Affairs Office) Somba Opu District, Gowa Regency. The research approach used by the researcher is the Islamic Counseling Guidance Approach. Primary data sources used by researchers are religious instructors including, Hj. Husnawiah (instructor), Bapak Suharman (instructor), Darul Aska (instructor) and several additional informants such as Bp. Rasyiduddi as Head of KUA, Saiful Hasan (client), Nurul (client), Azalia (client), Alif Imran (client), Dr. Aldam Rajab (Principal). Secondary data sources used are theses, journals, literature, and other data sources that can be used as a complement. Data collection methods used by researchers are observation, interviews, and documentation. Data analysis was carried out using the reduction and presentation stages.